2018
DOI: 10.1681/asn.2017111185
|View full text |Cite
|
Sign up to set email alerts
|

Transethnic, Genome-Wide Analysis Reveals Immune-Related Risk Alleles and Phenotypic Correlates in Pediatric Steroid-Sensitive Nephrotic Syndrome

Abstract: Steroid-sensitive nephrotic syndrome (SSNS) is a childhood disease with unclear pathophysiology and genetic architecture. We investigated the genomic basis of SSNS in children recruited in Europe and the biopsy-based North American NEPTUNE cohort. We performed three ancestry-matched, genome-wide association studies (GWAS) in 273 children with NS (Children Cohort Nephrosis and Virus [NEPHROVIR] cohort: 132 European, 56 African, and 85 Maghrebian) followed by independent replication in 112 European children, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
75
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 56 publications
(62 reference statements)
10
75
1
Order By: Relevance
“…These results revealed that HCG23 on chromosome 6 plays a major role in adenocarcinoma of the lung. And according to previous study, HCG23 was also supported participating immune-related diseases (Debiec et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…These results revealed that HCG23 on chromosome 6 plays a major role in adenocarcinoma of the lung. And according to previous study, HCG23 was also supported participating immune-related diseases (Debiec et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…1,10 Two of the loci described in the work by Debiec et al 8 were also within the HLA-DR/DQ region, and all three loci remained significant when controlled for HLA haplotype and these previously discovered risk alleles at the HLA-DQA1 locus. Debiec et al 8 also showed that having more disease-associated variants was associated with decreased age at disease onset and increased likelihood of complete remission. Both characteristics are strongly associated with SSNS, consistent with the notion that the associations reported are indeed with an SSNS and not an SRNS phenotype.…”
mentioning
confidence: 84%
“…Although it requires more sophisticated statistical genetics, the approach can uncover significant associations with loci of interest that would otherwise elude identification for rare diseases with complex inheritance patterns. 6,7 In this issue of the Journal of the American Society of Nephrology, Debiec et al 8 performed just such a transethnic genome-wide association study of SSNS, resulting in the discovery of three genetic loci in the HLA region with a lead risk allele upstream of HLA-DQB1.…”
mentioning
confidence: 99%
“…Conversely, systemic diseases, such as hypertension, may be driven by genes that primarily affect kidney function (20). Common variation in immune regulatory genes seems to affect the risk of various glomerular phenotypes (21). Diabetes, the most common cause of CKD, is the result in large part of combinations of variation in nonkidney genes; the verdict is still out on whether susceptibility to nephropathy in the setting of diabetes is driven primarily by genes directly affecting the kidney (22,23).…”
Section: Kidney Disease?mentioning
confidence: 99%